Antimicrobial Screening of Commercial Eggs and Determination of Tetracycline Residue Using Two Microbiological Methods - Idowu, Fagbamila; Junaid, Kabir; Paul, Abdu; Gabriel, Omeiza; Paul, Ankeli; Sati, Ngulukun; Maryam, Muhammad; Jarlath, Umoh (International Journal of Poultry Science, 2010)
Thirty commercial layer farms were surveyed to obtain information on drug use and to screen eggs for antimicrobial residues. Tetracycline residue was specifically tested using a commercial test kit. The study indicated that up to a third of farmers (33.3%) were not adhering to the recommendation on drug use and thereby allowing drug residues in eggs. Of the 900 commercial eggs screened, 3.6% tested positive for antimicrobial residues but only 0.1% tested positive for tetracycline residue. The low level of tetracycline residue detected in this study is an indication of the declining use of this antibiotic in the poultry industry perhaps due to the increasing availability of cheaper alternatives. There is a need for strict regulation of veterinary drug in order to guarantee food safety and effective use. To ensure compliance with drug use in Nigeria, routine surveillance must be conducted using simple detection methods.